Nitric oxide and Ca2+-activated high-conductance K+ channels mediate nothofagin-induced endothelium-dependent vasodilation in the perfused rat kidney. (25th August 2020) - Marques, Aline Aparecida Macedo; da Silva, Claudio Henrique Francisconi; de Souza, Priscila; de Almeida, Camila L.B.; Cechinel-Filho, Valdir; Lourenço, Emerson L.B.; Gasparotto Junior, Arquimedes
Abstract: Nothofagin is a natural 3′- C -β-D-glucoside of the polyphenol phloretin that is mainly found in Aspalathus linearis, Nothofagus fusca, and Leandra dasytricha . In recent years, nothofagin has been described as a potential therapeutic agent for renal disorders, but the mechanisms that are involved in its renoprotective effects remain unclear. In the present study, perfused rat kidneys were used to test the hypothesis that nothofagin causes the direct relaxation of renal arteries. The molecular mechanisms that underlie these vascular effects were also investigated. The left kidney from Wistar rats was coupled in a perfusion system and continuously perfused with physiological saline solution (PSS). Initially, preparations with and without the endothelium were contracted with phenylephrine and received injections of 1–300 nmol nothofagin. The preparations were then perfused with PSS that contained phenylephrine plus KCl, indomethacin, l -NAME, tetraethylammonium, glibenclamide, 4-aminopyridine, iberiotoxin, charybdotoxin, and apamin. After 15 min under perfusion, nothofagin was injected again. In preparations with an intact endothelium, nothofagin dose-dependently reduced perfusion pressure. Endothelium removal or the inhibition of nitric oxide synthase by l -NAME prevented the vasodilatory effect of nothofagin at all doses tested. Perfusion with PSS that contained KCl or tetraethylammonium chloride also abolished the vasodilatory effect of nothofagin. Treatment with glibenclamide, 4-aminopyridine, and apamin did not affect the vasodilatory effect of nothofagin. Iberiotoxin (selective Ca 2+ -activated high-conductance K + channel [KCa1.1] blocker) and charybdotoxin (selective KCa1.1 and Ca 2+ -activated intermediate-conductance K + channel [KCa3.1] blocker) application blocked the vasodilatory effect of nothofagin at all doses tested, pointing to a predominant role for KCa1.1 in the action of nothofagin. However, these data cannot exclude a potential contribution of endothelial KCa3.1 channel in the nothofagin-induced vasodilation. Overall, our findings indicate that nothofagin induces vasodilation in renal arteries, an effect that is mediated by Ca 2+ -activated high-conductance K + channels opening and endothelial nitric oxide production. Highlights: Nothofagin is a natural 3′- C -β-D-glucoside of the polyphenol phloretin. Nothofagin has been described as a therapeutic agent for renal disorders. We assessment the vasodilatory effects of nothofagin in isolated kidney. Our findings indicate that nothofagin induces vasodilation in renal arteries. These effects are mediated by nitric oxide and Ca 2+ -activated BK and IK channels.